Diseño de un packaging para la distribución de la panela granulada de las parroquias de Palo Quemado / Las Pampas del cantón Sigchos provincia de Cotopaxi. - Guillen Mena, Denis Vinicio (2020)
This project focuses on the association "Flor de Caña", which is located between the parishes Palo Quemado - Las Pampas, belonging to the Sigchos canton, Cotopaxi province - Ecuador, which has factors of climatic variation and fertile land, which they favor the conditioning to cultivate the sugar cane. This association has as preference to supervise each one of the procedures within the production of panela, encouraging the inhabitants to the good use of the agricultural product within the farm field. Granulated panela stands out for being organic and containing a high nutritional value that benefits human consumption. Together with the “Flor de Caña” association, it has been necessary to create a creative packaging design, considering the research and knowledge of the graphic design field, projecting on the demand of the product, through a design that qualifies and personify the association in a commercial way with its characteristics of the product, and of the place of precedence, fulfilling the expectations and demands of the consumer, expanding the marketing and distribution of granulated panela nationwide, promoting economic development to the parishes within the productive scope taking into account that there are several products that meet the same purpose of granulated panela, however they do not have an adequate packaging structure, so it has been necessary to capture their own forms that represent the area to create the structure adequate packaging.